2018
DOI: 10.28991/cej-03091141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature in Different Initial Duration Time for Soft Clay Stabilized by Fly Ash Based Geopolymer

Abstract: When soft clay soils are included in engineering projects, it’s stabilized usually with some kinds of admixtures named as stabilizers. The common stabilizers that highly practiced are OPC, lime, high calcium fly ash (FA), etc. Each one of these stabilizers has its shortcomings. Geopolymers are the product of alkali activated aluminosilicate sources that excelled as an alternative to ordinary binders due to its sustainability, low cost and good mechanical properties. This study investigates the effects of some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The Geopolymer produced with metakaolin are considered a ''model-system" without the complexities introduced by the use of fly ash, slags, and other alternative raw materials, which contain several hard-to-characterize amorphous phases. Fly ash, for example, is not a well-defined material, but it comprises several crystalline and vitreous phases [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Geopolymer produced with metakaolin are considered a ''model-system" without the complexities introduced by the use of fly ash, slags, and other alternative raw materials, which contain several hard-to-characterize amorphous phases. Fly ash, for example, is not a well-defined material, but it comprises several crystalline and vitreous phases [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common clay is the kaolin which upon thermal activation within temperature range of 650°C to 800°C becomes metakaolin (Pera, 2001). Metakaolinbased geopolymer is said to be purer and can be readily characterised hence, they are referred to as modelsystem without the complexities associated with other aluminosilicate source such as fly ash (Shihab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the relevant literature revealed that the potential role of the alkali solutions in activating coal ashes was considered by several recent studied to enhance and stabilize soils such as clay soil [19] and silty sand soil [20].…”
Section: Introductionmentioning
confidence: 99%